Caspar negatively regulates anti-bacterial immunity by controlling the nuclear translocation of Relish in Chinese mitten crab (Eriocheir sinensis). Issue 136 (May 2023) - Luo, Zhi; Qin, Yu-Kai; Zhao, Ke; Nan, Xing-Yu; Li, Wei-Wei; Li, Er-Chao; Wang, Qun
Abstract: Caspar, a homolog of the Fas-associated factor 1 (FAF1) family, contains an N -terminal ubiquitin interaction domain, a ubiquitin-like self-association domain, and a C -terminal ubiquitin regulatory domain. Caspar has been reported to be involved in the antibacterial immunity of Drosophila, which is unclear whether it is involved in the antibacterial immune process of crustaceans. In this article, we identified a Caspar gene in Eriocheir sinensis and named it Es Caspar. Es Caspar positively respond to bacterial stimulation and downregulate the expression of certain associated antimicrobial peptides by inhibiting the nuclear translocation of Es Relish. Thus, Es Caspar might be a suppressor of the immune deficiency (IMD) pathway that prevents over-activation of the immune system. Indeed, excess Es Caspar protein in crabs reduced resistance to bacterial infection. In conclusion, Es Caspar is a suppressor of the IMD pathway in crabs that plays a negative regulatory role in antimicrobial immunity. Highlights: The Eriocheir sinensis Caspar gene was cloned and characterized. Es Caspar inhibited the nuclear translocation of Relish. This inhibition downregulated antimicrobial peptide expression. Es Caspar is a suppressor of the immune deficiency pathway. Es Caspar negatively regulates antimicrobial immunity.